Transactions on Petri Nets and Other Models of Concurrency I - van der Aalst, Wil M. P.; Billington, Jonathan (Transactions on Petri Nets and Other Models of Concurrency, 2008)
These Transactions publish archival papers in the broad area of Petri nets and other models of concurrency, ranging from theoretical work to tool support and industrial applications. ToPNoC issues are published as LNCS volumes, and hence are widely distributed and indexed. This Journal has its own Editorial Board which selects papers based on a rigorous two stage refereeing process. ToPNoC contains: - Revised versions of a selection of the best papers from workshops and tutorials at the annual Petri net conferences - Special sections/issues within particular subareas (similar to those published in the Advances in Petri Nets series) - Other papers invited for publication in ToPNoC - Papers submitted directly to ToPNoC by their authors This is the first volume of ToPNoC. It contains revised and extended versions of a selection of the best papers from the workshops held at the 28th International Conference on Applications and Theory of Petri Nets and Other Models of Concurrency, which took place in Siedlce, Poland, June 25-29, 2007. The material has been selected and evaluated by the two Workshop and Tutorial Chairs, Wil van der Aalst and Jonathan Billington, in close cooperation with the chairs of the individual workshops. The 13 papers in this volume cover a wide range of concurrency-related topics, including: teaching concurrency; process languages; process mining; software engineering; state space visualisation techniques; timed Petri nets; unfolding techniques and hardware systems. Thus, this volume gives a good overview of the state of the art in concurrency research.